Afghan returnees as actors of change? - van Houte, M (Refugee Studies Centre, University of Oxford, 2014)
Afghan returnees from industrialised countries are expected to contribute to development and peace building in Afghanistan. However, which category of returnee is expected to bring what kind of change often remains under-defined.